T risk tolerance, perceived usefulness, and intention to subscribe to digital unit trust / Sunitawati Karim ... [et al.] - Karim, Sunitawati; Zakaria, Nor Balkish; Rohaizat, Emeer Danial; Abdullah, Dewi Fariha Earnest; Baykal, Elif; -, Rizqa Anita (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2024)
The online subscription intention among the individual investors in Malaysia via the Unit Trust Online Digital Service (UTODS) has not been widely investigated. Understand the inclination of the subscription intention amid rising online fraud was significant to all the industry players as it defined the market's strength and sustainability. A quantitative survey of 384 experienced online investors was conducted. Data were analyzed using Exploratory Factor Analysis (EFA) to identify key constructs, followed by Confirmatory Factor Analysis (CFA) for validation. Structural Equation Modeling (SEM) revealed significant relationships between perceived usefulness, risk tolerance, and subscription intention. The findings confirmed the moderating role of risk tolerance was influenced investors' decisions, offering practical insights for enhancing online investment platforms.